VIRTUE ETHICS AND THE DUTY OF VERACITY IN PHYSICIAN-PATIENT RELATIONSHIP (2014)
The duty of veracity or truth-telling, a condition in medical practice which requires that patients be told the truth at all times about their medical diagnosis has generated ethical challenges in modern medical practice. Previous studies have examined the problem of veracity using principle-based ethical theories like deontologism and teleologism. These theories, however, failed to provide a basis for resolving the dilemma of truth-telling because of the conflicting nature of the principles they articulate and their disregard for the character of the moral agent, which, actually, provides the grounding for appropriate action. This study, therefore, proposed virtue ethics as an appropriate theory that provides the basis for mediating in the dilemma of veracity in physician-patient relationship, with a view to showing the crucial role that character plays in medical decision-making. Aristotle’s theory of phronesis, which emphasises the role of practical wisdom that derives from character in decision-making, was adopted as framework. Ten relevant texts in medical and applied ethics, particularly Beauchamp and Childress’s Principle of Biomedical Ethics (PBE), Gorovitz’s Moral Problems in Medicine (MPIM) and Drane’s Becoming a Good Doctor: The Place of Virtue and Character in Medical Ethics (BGD), and four in traditional ethics, particularly Aristotle’s Nicomachean Ethics (NE) were purposively selected because they deal extensively with ethics and the issue of veracity in medical practice. Conceptual analysis was used to clarify key concepts like veracity, deontologism and teleologism, while critical method was adopted in examining earlier approaches to the issue of veracity and proposing virtue ethics as the basis for mediating the dilemma of truth-telling in physician-patient relationship. Most texts on medical and applied ethics revealed a consequentialist position: that a physician has an overriding moral duty to prevent harm, which supercedes the weaker obligation to tell the truth at all times (MPIM and PBE). Texts on traditional ethics revealed that the major approaches to resolving the dilemma of veracity fall under two categories: deontologism which emphasises duty and teleologism which emphasises consequences. These approaches are inadequate because of the rigid and conflicting nature of the principles they advance, and their disregard for the character of the moral agent. Critical interrogation showed that character is essential in physician’s relationship with patients as it aids the physician to apply practical wisdom when principles fail (NE and BGD). Consequently, the doctor is bound to higher ideals and virtues such as honesty, compassion, dignity and integrity, and is, therefore, able to go beyond the normal expectations of deontological and teleological principles in his relationship with patients (BGD). Virtue ethics helps in developing good character traits and habits which correspond to the higher ideals and virtues that a physician must necessarily cultivate in order to respond in a morally appropriate manner when faced with the dilemma of veracity or truth-telling. Virtue ethics promotes good character traits in persons, providing grounds for morally appropriate actions when faced with the dilemma of veracity. Therefore, virtue ethics offers a more pragmatic ethical framework for resolving the dilemma of truth-telling in physician-patient relationship.